العلاقة بين الولاء التنظيمي والرضا الوظيفي للكادر التمريضي في مشفى تشرين الجامعي - اصبيره, ولاء هاشم (Latakia University Journal -Medical Sciences Series, 2019)
The study aimed to determine the relationship between organizational commitment and job satisfaction of nursing staff in Tishreen university Hospital in Lattakia City. The sample consisted of (225) nurses who were presented during the data collection period and agreed to participate (convenience sample). The researcher used two tools to collect research data, where as , the researcher developed organizational commitment questionnaire and job satisfaction questionnaire based on modern references related to research topic. After the data were collected and unloaded, they were statistically processed and tabulated using SPSS version 20. The most important results of the study were that the level of nursing staff' s organizational commitment at Tishreen University Hospital was totally moderate, as well as the level of nursing staff 's job satisfaction at Tishreen University Hospital was totally moderate. There was strong statistically significant relationship between organizational commitment and job satisfaction of nursing staff. هدفت الدراسة إلى تحديد العلاقة بين الولاء التنظيمي والرضا الوظيفي للكادر التمريضي في مشفى تشرين الجامعي في مدينة اللاذقية. حيث تكونت العينة من (225) ممرض وممرضة من العاملين في مشفى تشرين الجامعي , ممن تواجدوا أثناء فترة تجميع البيانات (العينة المتاحة) ووافقوا على المشاركة في البحث. استخدمت الباحثة أداتين لجمع بيانات البحث, حيث طورت الباحثة استبيان الولاء التنظيمي واستبيان الرضا الوظيفي بناء على المراجع الحديثة المتعلقة بموضوع البحث ، وبعد جمع و تفريغ البيانات تمت معالجتها إحصائياً وجدولتها باستخدام البرنامج الاحصائي SPSS النسخة 20. كان من أهم النتائج: إنّ مستوى الولاء التنظيمي للكادر التمريضي في مشفى تشرين الجامعي كان متوسطاً بشكل عام, كما كان مستوى الرضا الوظيفي للكادر التمريضي مشفى تشرين الجامعي متوسطاً بشكل عام, مع وجود علاقة قوية ذات دلالة احصائية بين الولاء التنظيمي للكادر التمريضي في مشفى تشرين الجامعي ورضاهم الوظيفي.